Environmental technologies used for the mitigation of industrial environmental impacts - Santos, Claudson Gomes; Carvalho, Eloiza Suimay Azevedo (Ciência e Natura, 2022)
With the growth of the world population, constant technological evolution and consequent change in the habits of our society, human activity is gradually increasing its capacity of alteration to the environment. Small acts of environmental preservation result in great feats for the ecosystem, for humanity and are preludes for the continuity of life. This study discusses the dispersion of pollutants caused by industries, the importance of the remediation technologies used, which can prevent and / or mitigate the impacts that are caused to the environment. This study is a comparison between end-of-pipe technologies and cleaner production, which are the most used by industries. It was based on the environmental impacts caused by the industries and on the most used remediation technologies as mechanisms to reduce or prevent these impacts.